2016
DOI: 10.1080/09638237.2016.1207226
|View full text |Cite
|
Sign up to set email alerts
|

Art therapy for patients with depression: expert opinions on its main aspects for clinical practice

Abstract: Experts in the field of art therapy considered that the main aspect of clinical practice in art therapy for patients with depression is that art themes should promote expression related to both to depression and personal history.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…Research conducted by Kneer et al [ 105 ] indicates that due to in-game success and challenge, the game Team Fortress 2 can elicit positive postgame mood, and these mood benefits are conferred among players of all skill levels. Art therapy, with its use of visual artistic creation to focus on creativity, symbolism of colors or shapes, and the exploration and expression of personal emotions, could also be seen to permeate into commercial video games with positive outcomes for individuals with depression [ 106 , 107 ]. Distinctly designed gaming environments accompanied by tailored soundtracks serve as a safe setting for the exploration and interpretation of emotional states elicited by game graphics.…”
Section: New Perspective: the Case For Commercial Video Gamesmentioning
confidence: 99%
“…Research conducted by Kneer et al [ 105 ] indicates that due to in-game success and challenge, the game Team Fortress 2 can elicit positive postgame mood, and these mood benefits are conferred among players of all skill levels. Art therapy, with its use of visual artistic creation to focus on creativity, symbolism of colors or shapes, and the exploration and expression of personal emotions, could also be seen to permeate into commercial video games with positive outcomes for individuals with depression [ 106 , 107 ]. Distinctly designed gaming environments accompanied by tailored soundtracks serve as a safe setting for the exploration and interpretation of emotional states elicited by game graphics.…”
Section: New Perspective: the Case For Commercial Video Gamesmentioning
confidence: 99%
“…This current study revealed that four sessions of creative art therapy had a significant positive influence on levels of depression, anxiety, and stress. A potential explanation for these results is that different creative art tasks with different themes were equally important and allowed patients to address their psychological status, including their thoughts, feelings, and physical symptoms to meet their treatment needs ( Blomdahl et al, 2016 ). These study results resonate with the literature, which reported that the use of creative art therapy in clinical practice is an opportunity for individuals to express themselves verbally and nonverbally and serves as a catalyst for verbal dialogue ( Blomdahl et al, 2016 ; Michaels, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is proven to help combat the chemical imbalances in the brain that may lead to depression. It has been found to be influential in dealing with patients with depression (Blomdahl, et al, 2016). Depression being a complex syndrome with symptoms such as low mood, low self-esteem, and performing art therapy acts as an important method of treatment for depression (Blomdahl, et al, 2016).…”
Section: Constructive Advantages Of Art Therapymentioning
confidence: 99%